Hypoxia-alleviated sonodynamic therapy based on a hybrid protein oxygen carrier to enhance tumor inhibition. (2nd December 2021) - Yin, Ting; Yin, Jia; Ran, Hui; Ren, Yaguang; Lu, Chengyu; Liu, Lanlan; Shi, Qingxia; Qiu, Yuzhi; Pan, Hong; Ma, Aiqing
Abstract : Sonodynamic therapy (SDT) is a highly attractive therapy due to its advantages of being non-invasive and having good penetration depth, but tumor hypoxia extremely restricts its therapeutic effect. Abstract : Sonodynamic therapy (SDT) is a highly attractive therapy due to its advantages of being non-invasive and having good penetration depth, but tumor hypoxia extremely restricts its therapeutic effect. Here, a novel oxygen-enhanced hybrid protein nanosonosensitizer system (MnPcS@HPO) is designed using human serum albumin (HSA) and hemoglobin (Hb) through disulfide reconfiguration, followed by encapsulating Mn-phthalocyanine (MnPcS), aiming to develop O2 self-supplementing nanoparticles (NPs) for enhanced SDT. Benefitting from the O2 -carrying ability of Hb and the tumor-targeting property of HSA, the MnPcS@HPO NPs are able to target tumor sites and alleviate hypoxia. Meanwhile, as a sonosensitizer, MnPcS is excited under US irradiation and activates dioxygen to generate abundant singlet oxygen ( 1 O2 ), resulting in oxidative damage of tumor cells. Guided by photoacoustic and magnetic resonance dual-modal imaging, the MnPcS@HPO NPs alleviate tumor hypoxia and achieve good SDT efficiency for suppressing tumor growth. This work presents a novel insight into enhanced SDT antitumor activity through natural protein-mediated tumor microenvironment improvement.